2020
DOI: 10.1101/2020.05.25.112896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted CRISPR screening identifies PRMT5 as synthetic lethality combinatorial target with gemcitabine in pancreatic cancer cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most challenging cancer to treat. Due to the asymptomatic nature of the disease and ineffective drug treatment modalities, the survival rate of PDAC patients remains one of the lowest. The recurrent genetic alterations in PDAC are yet to be targeted; therefore, identifying effective therapeutic combinations is desperately needed. Here, we performed an in vivo CRISPR screening in a clinically relevant patient-derived xenograft (PDX) model system to iden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…JNJ-64619178 distinctly reduced the symmetrical dimethylation of histone H4R3 (Supplemental Figure 5A). Recent data demonstrated that PRMT5 blockade induces a DNA damage response in PDAC cells (27). Therefore, we investigated phosphorylation of H2AX as a surrogate for the DNA damage response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…JNJ-64619178 distinctly reduced the symmetrical dimethylation of histone H4R3 (Supplemental Figure 5A). Recent data demonstrated that PRMT5 blockade induces a DNA damage response in PDAC cells (27). Therefore, we investigated phosphorylation of H2AX as a surrogate for the DNA damage response.…”
Section: Resultsmentioning
confidence: 99%
“…PRMT5 is a type II protein arginine methyltransferase catalyzing symmetrical dimethylation of arginines in histones and other proteins (24). High PRMT5 expression was recently linked to worse survival of patients with PDAC (25)(26)(27). To underpin the connection of MYC to PRMT5, we analyzed curated mRNA expression data sets (20,28).…”
Section: Resultsmentioning
confidence: 99%
“…e results of this analysis fully confirm that gemcitabine plus platinum combined regimen can significantly prolong the total and progression-free survival of patients with advanced NSCLC compared with other platinum-containing schemes. In 2007, Grossi et al's metaanalysis compared the activity of gemcitabine with three other third-generation platinum-containing chemotherapy programs [15]. e meta-analysis included 48 studies, with 6,671 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another example, Wei and colleagues used a targeted CRISPR screening approach on a PDTX model established from poorly differentiated metastatic pancreatic ductal adenocarcinoma, known to contain KRAS, p53 and SMAD4 mutations. They identified PRMT5 as a therapeutic target for cells co-treated with Gemcitabine chemotherapy (Wei et al, 2020).…”
Section: In Vivo Functional Genomic Screensmentioning
confidence: 99%